Interpretation of Serum Creatine Kinase in Suspected Myocardial Infarction. Issue 5946 (21st December 1974) - Scott, B. B.; Simmons, A. V.; Newton, K. E.; Payne, R. B.
Abstract : Serum creatine kinase (CK) was measured in blood donors, patients admitted to hospital with suspected myocardial infarction, and healthy hospital personnel to investigate the normal range, the daily variation in healthy people, and the effect of intramuscular injections of pentazocine or diamorphine. There was considerable daily variation in the healthy controls, apparently related to exercise. In defining both the normal range and the significance of day-to-day increases in the serum CK account should be taken of this factor. An upper limit of normal of 210 IU/1. Should apply to previously ambulant patients and of 165 IU/1. to patients previously at rest. An increase greater than 85% in successive daily values is uncommon in health. Intramuscular injections of both pentazocine and diamorphine caused a significant rise in the serum CK in six out of 25 patients. The highest rise observed was from 64 IU/1. to 395 IU/1. Caution is therefore urged in the diagnosis of myocardial infarction from the serum CK values when these intramuscular injections have been given.